RUSSIAN LANGUAGE AS A FACTOR OF INTERETHNIC INTEGRATION IN THE CIS COUNTRIES - Barno Badalova (Bright Mind Publishing, 2025)
The Russian language plays a significant role in the interethnic integration of the Commonwealth of Independent States (CIS) countries, serving as a bridge for communication, education, and cultural exchange. As a historically widespread language in the post-Soviet space, Russian continues to function as a medium for political dialogue, economic cooperation, and academic interaction. This paper explores the role of the Russian language in fostering interethnic integration within CIS countries, highlighting its impact on national identity, education policies, and social cohesion. The study examines the linguistic landscape of the region, discussing the challenges and opportunities associated with the preservation and promotion of Russian in multilingual environments. Additionally, the paper addresses how language policies in different CIS countries influence the perception and usage of Russian among various ethnic groups. The research aims to provide a comprehensive analysis of the Russian language as a tool for maintaining unity and fostering multicultural dialogue across post-Soviet nations.
Keywords: Russian language, interethnic integration, CIS countries, language policy, cultural identity, multilingualism, linguistic communication, social cohesion.